Sistem Presensi Mahasiswa Berbasis QR Code di STMIK “AMIKBANDUNG” - Amal Julio Rafila; Tedjo Darmanto; Rudi Kurniawan (Journal of Information Technology, 2020)
One of the important things that need to be considered in student assessment is the problem of student presence. The student attendance process that is very commonly done by universities is recording attendance manually, as currently applied by STMIK "AMIKBANDUNG". QR Code technology is a technology that can encode and decode all types of data into an image in the form of a code and can be read with a smartphone, this is very suitable for use as data validation, which is usually used for digital payment methods today. With these advantages QR Code technology can be implemented as well as supporting media in the smooth process of lecture attendance, This is interesting to the author to conduct research on lecture presence design using QR Code technology, with QR Code technology, each student is expected to no longer need to sign the form absent because the presence data will be identified automatically via a smartphone that can scan the QR Code and be stored in the system database.